2009
DOI: 10.1097/qai.0b013e3181b98430
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of a Urine Lipoarabinomannan Test for Tuberculosis in Hospitalized Patients in a High HIV Prevalence Setting

Abstract: Background Effective tuberculosis (TB) control in HIV-prevalent settings is hindered by absence of accurate, rapid TB diagnostic tests. We evaluated the accuracy of a urine lipoarabinomannan (LAM) test for TB diagnosis in South Africa. Methods Hospitalized adults with signs and/or symptoms of active TB were enrolled. Sputum smear microscopy and mycobacterial culture, mycobacterial blood culture, and HIV testing were performed. A spot urine specimen was tested for LAM. Results 499 participants were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
111
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 14 publications
10
111
2
1
Order By: Relevance
“…However, we also found that LAM was positive in 41% of smear-negative specimens; this is a relatively large incremental yield compared with smear microscopy. This suggests that the LAM assay and smear microscopy may detect different groups of TB patients, and might be best used in combination, as was reported by SHAH et al [23].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, we also found that LAM was positive in 41% of smear-negative specimens; this is a relatively large incremental yield compared with smear microscopy. This suggests that the LAM assay and smear microscopy may detect different groups of TB patients, and might be best used in combination, as was reported by SHAH et al [23].…”
Section: Discussionsupporting
confidence: 63%
“…Meta-regression was performed using the overall proportion of HIV-positive TB suspects in each study as an independent TESSEMA [18] BOEHME [19] REITHER [20] MUTETWA [21] SHAH [23] DHEDA [25] HAMASUR [17] TESSEMA [18] BOEHME [19] REITHER [20] MUTETWA [21] SHAH [23] DHEDA [25] TESSEMA [18] BOEHME [19] REITHER [20] MUTETWA [21] LAWN [22] SHAH [23] DALEY [24] DHEDA [25] QUADAS criteria…”
Section: Subgroup Analyses and Meta-regressionmentioning
confidence: 99%
“…Our group and others have recently reported on the qualitative diagnostic accuracy of this urine LAM test (9,10,16). Urine LAM test sensitivity, while imperfect, appears to be higher than that of sputum smear microscopy, and the test performs with a high positive predictive value in populations with high HIV and TB prevalence (9,12,16). However, quantitative urine LAM test results have not been studied fully.…”
mentioning
confidence: 96%
“…Sputum smear microscopy is widely utilized to diagnose active TB but has impaired sensitivity and detects less than half of HIV-TB coinfection cases (2,6,8). Mycobacterial culture is the laboratory standard for diagnosis but is not widely available in resource-constrained settings and can take weeks to determine a positive result.The detection of lipoarabinomannan (LAM), a 17.5-kDa glycolipid component of the mycobacterial cell wall, is an attractive approach to diagnosing active TB (1,7,9,15,16). LAM is released from metabolically active mycobacteria and is detectable intact in urine (1, 7).…”
mentioning
confidence: 99%
“…However, one study showed high sensitivity for detecting TB in smearpositive sputum from HIV-infected subjects, using the AMPLI-COR PCR (Roche Diagnostic Systems, Branchburg, NJ) (99.7%), and no significant difference in sensitivity compared with smear-negative culture-positive specimens from HIV-negative subjects (89 vs. 95%) (108). Urine detection of the MTb cell wall component lipoarabinomannan may improve detection in smear-negative HIV-infected patients with advanced immunosuppression in a high-prevalence setting (109,110). Serological tests currently have no proven role in the diagnosis of active TB with or without HIV (111) and IFN-g release assays (IGRAs) do not help to distinguish latent from active TB (63).…”
Section: Active Tb Disease Diagnosis In Hivmentioning
confidence: 99%